Alternative Healthy Eating Index 2010, Dietary Inflammatory Index and risk of mortality: results from the Whitehall II cohort study and meta-analysis of previous Dietary Inflammatory Index and mortality studies‡. Issue 3 (14th August 2017) - Shivappa, Nitin; Hebert, James R.; Kivimaki, Mika; Akbaraly, Tasnime
Abstract: We aimed to examine the association between the Alternative Healthy Eating Index updated in 2010 (AHEI-2010), the Dietary Inflammatory Index (DII TM ) and risk of mortality in the Whitehall II study. We also conducted a meta-analysis on the DII-based results from previous studies to summarise the overall evidence. Data on dietary behaviour assessed by self-administered repeated FFQ and on mortality status were available for 7627 participants from the Whitehall II cohort. Cox proportional hazards regression models were performed to assess the association between cumulative average of AHEI-2010 and DII scores and mortality risk. During 22 years of follow-up, 1001 participants died (450 from cancer, 264 from CVD). Both AHEI-2010 (mean=48·7 (sd 10·0)) and DII (mean=0·37 (sd 1·41)) were associated with all-cause mortality. The fully adjusted hazard ratio (HR) persd, were 0·82; 95 % CI 0·76, 0·88 for AHEI-2010 and 1·18; 95 % CI 1·08, 1·29 for DII. Significant associations were also observed with cardiovascular and cancer mortality risk. For DII, a meta-analysis (using fixed effects) from this and four previous studies showed a positive association of DII score with all-cause (HR=1·04; 95 % CI 1·03, 1·05, 28 891deaths), cardiovascular (HR=1·05; 95 % CI 1·03, 1·07, 10 424 deaths) and cancer mortality (HR=1·05; 95 % CI 1·03, 1·07, n 8269).The present study confirms the validity to assess overall diet through AHEI-2010 and DII in the Whitehall II cohort and highlights the importance of considering diet indices related to inflammation when evaluating all-cause, cardiovascular and cancer mortality risk.